Nutritional Status and Compliance with Blood Supplemental Tablets as a Cause of Anemia in Pregnant Women - Odilia Esem (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Health issues that might arise during pregnancy include anemia. Pregnant women who have good nutritional status do not experience anemia. Conversely, pregnant women with poor nutritional status can cause anemia if blood-supplemented tablets that are not consumed regularly can result in pregnant women experiencing iron deficiency which is closely related to the incidence of anemia. This study aims to determine the relationship between nutritional status and adherence in consuming blood supplement tablets with anemia in third-trimester pregnant women. This research is a form of analytic survey research with a cross-sectional analytical design research approach. This research was conducted from March to April 2023. The sample in this study were all third-trimester pregnant women at the Sikumana Health Center, 50 people using a total sampling technique. There was no significant relationship between nutritional status and anemia in third-trimester pregnant women with a p-value (0.050), while there was a significant relationship with anemia adherence with a p-value (of 0.000). Based on the results of the study, it was concluded that there was no statistically significant relationship between nutritional status and the incidence of anemia in third-trimester pregnant women. In the analysis of compliance with anemia, there was a statistically significant relationship between adherence to consuming blood supplement tablets and the incidence of anemia in third-trimester pregnant women.